How does round goby (Neogobius melanostomus) affect fish abundance in the Swedish coastal areas of the Baltic Sea? - Rahmat Naddafi; Ann-Britt Florin (PLoS ONE, 2025)
Quantifying the effects of species invasions is particularly challenging, as it requires accurate measurements of the ecosystem before and after the invasion. The round goby (Neogobius melanostomus), a highly successful invasive species from the Ponto-Caspian region, has had significant ecological impacts on native communities in the invaded ecosystems. However, there are currently no studies examining the impact of the round goby invasion on the abundance of coastal fish in the Baltic Sea. Using 17–23 years of monitoring data from four areas, we quantified the changes in fish abundance (mostly representing coastal fish indicators and key coastal fish species) associated with the round goby invasion in the Swedish coastal areas. A generalized additive mixed model suggests that round goby invasion will lead to an increase in the abundance of perch, cyprinids, piscivores, and ruffe, while whitefish and flounder abundance will decrease. In addition, the abundance of sprat and herring may not be affected by round goby invasion. Abundance of perch, cyprinids, flounder, perch ( ≥20 cm total length), cod, pikeperch, and pike were increased with water temperature and were decreased with water depth and wave exposure. We observed a decreasing trend in the abundance of whitefish, sprat, and herring with an increase in water temperature and a decrease in water depth. Given the low abundance of several piscivorous species in the Baltic Sea and the role of predators to control exotic prey, reinforcing piscivore populations might be useful for the Baltic Sea ecosystem and regulating round goby populations at a local scale.